GIS applications for the investigation of hydrometeorological and biochemical conditions of coastal areas - KARAGEORGIS, A.P.; MIKHAILOV, N.; DRAKOPOULOU, P.; VORONTSOV, A.; ANAGNOSTOU, CH.; LYKIARDOPOULOS, A. (Mediterranean Marine Science, 2000)
The paper discusses the use of Geographical Information Systems (GIS) in the aspects of marine environmental research, as approached by Russian and Greek groups. The scientific teams apply the same GIS platform in both cases, but with a different orientation, according to the particular driving forces of the projects involved. In general, the Russian team manipulates GIS as a subsystem of problem-oriented applications in order to enlarge the possibilities to run non-standard user programs. The subsystem of problem-oriented applications (POA) is designed for the following: (1) analysis of data and information to implement applied tasks; (2) preparation of output information products of the system in the form of hard and electronic copies in accordance with the required formats; and (3) dissemination of information products according to the users requirements. The Greek group focuses on the GIS use as a tool for joining different layers of spatial information in the marine area under investigation. Also, incorporated in the GIS is the drainage basin that supplies the marine area with water, sediment load and also human derived substances. Layers of hypsometry, bathymetry, hydrography, river network, roads, cities, satellite images etc., have been introduced into the system, obtaining significant feedback information. Also, there are developed the relations of the former layers with the marine sampling stations network and the database that describes the station's properties. The two groups benefit particularly by the exchange of ideas and methods, as different consideration is undertaken to resolve marine research issues.